Fine ultrastructural features of germ cells and spermatozoa during spermatogenesis in the European grayling, Thymallus thymallus (Teleostei, Salmoniformes, Salmonidae) - Dadras, Hadiseh; Dadras, Faranak; Imentai, Aiman; Malinovskyi, Oleksandr; Pěnka, Tomáš; Kolářová, Jitka; Policar, Tomáš (Frontiers in Veterinary Science, 2023)
This study aimed to examine the ultrastructure of spermatogenic stages and mature spermatozoa in the European grayling, Thymallus thymallus. The testes were examined microscopically with a transmission electron microscope to find out details of the structure and morphology of the grayling germ cells, spermatozoa and some somatic cells. The grayling testis has a tubular shape, with cysts or clusters of germ cells within seminiferous lobules. The spermatogenic cells, including spermatogonia, spermatocytes, and spermatids, can be found along seminiferous tubules. There are electron-dense bodies in germ cells from the primary spermatogonia to secondary spermatocyte stages. These undergo mitosis to reach the secondary spermatogonia stage, when they form primary and secondary spermatocytes. Spermatids undergo three different stages of differentiation during spermiogenesis, characterized by the level of chromatin condensation, elimination of cytoplasm, and the occurrence of the flagellum. The midpiece of spermatozoa is short and contains spherical or ovoid mitochondria. The sperm flagellum has an axoneme with nine doublets of peripheral microtubules and two central microtubules. The result of this study is valuable to be used as a standard reference for germ cell development, which is of great importance to get a clear insight into the process of grayling breeding practice.